Excessive Daytime Sleepiness in Depression and Obstructive Sleep Apnea: More Than Just an Overlapping Symptom - Zhang, Danwei; Zhang, Zhen; Li, Huihua; Ding, Kaimo (Frontiers in Psychiatry, 2021)
Excessive daytime sleepiness (EDS) is a significant public health concern, with obstructive sleep apnea (OSA) being a common cause, and a particular relationship exists with the severity of depression. A literature search on OSA, depression, and EDS was performed in PubMed. The chosen evidence was limited to human studies. Available evidence was systematically reviewed to ascertain the association of EDS with depression and OSA according to the general population and some specific population subgroups. In addition, effectiveness of continuous positive airway pressure (CPAP) was analyzed as a standard therapy for improving EDS and depression in patients with OSA. In the general population, patients with OSA, and some other subpopulations, the review contributed to: (1) delineating the prevalence of EDS; (2) substantiating the relationship of EDS and depression; (3) presenting the relationship between EDS and OSA; and (4) revealing that the duration of CPAP is crucial for its therapeutic effects in improving EDS and depressive symptoms in patients with OSA.